Enhanced glycolysis is associated with aggressive tumor phenotype and worse outcomes in hepatocellular carcinoma patients - Oshi, Masanori; Rog, Colin; Yan, Li; Endo, Itaru; Takabe, Kazuaki (Frontiers in Medicine, 2025)
BackgroundAdenosine Triphosphate (ATP) is mainly generated by oxidative phosphorylation in non-malignant cells, whereas malignant cells rely predominantly on glycolysis for energy production, known as the “Warburg effect.” This study used the gene set variation analysis (GSVA) algorithm to evaluate glycolysis signaling in hepatocellular carcinoma (HCC), and investigated its relationship with tumor aggressiveness and patient prognosis.MethodsEnhanced level of glycolysis signaling was measured using the “Hallmark-GLYCOLYSIS” gene set in the MSigDB, applied via GSVA across multiple independent HCC cohorts.ResultsThere was no significant difference in glycolysis signaling between HCC and other liver diseases in two cohorts. However, enhanced glycolysis signaling linked to gene sets associated with cell proliferation and cancer-promoting pathways, such as unfolded protein response, epithelial mesenchymal transition, and apoptosis, consistently in both cohorts. HCC with high glycolysis signaling score showed increased homologous recombination deficiency (p = 0.004), intratumor heterogeneity (p = 0.005), and mutation burden (p = 0.022). No consistent associations with glycolysis were observed with immune cells infiltration nor cytolytic activity, except for Th1 cells. Clinically, high glycolysis signaling correlated with advanced tumor stage and significantly worse survival outcomes, serving as an independent prognostic biomarker [hazard ratio (HR) = 6.78 and p < 0.001 in OS, HR = 6.56 and p = 0.027 in DSS].ConclusionElevated glycolysis signaling is linked to enhanced malignant pathways, genomic instability, and worse clinical outcomes in HCC, indicating its potential as a prognostic biomarker.